Dental management of a patient fitted with subcutaneous Implantable Cardioverter Defibrillator device and concomitant warfarin treatment - Altaf Hussain Shah; Hesham Saleh Khalil; Mohammed Zaheer Kola (Elsevier, 2015)
Automated Implantable Cardioverter Defibrillators (AICD), simply known as an Implantable Cardioverter Defibrillator (ICD), has been used in patients for more than 30 years. An Implantable Cardioverter Defibrillator (ICD) is a small battery-powered electrical impulse generator that is implanted in patients who are at a risk of sudden cardiac death due to ventricular fibrillation, ventricular tachycardia or any such related event. Typically, patients with these types of occurrences are on anticoagulant therapy. The desired International Normalized Ratio (INR) for these patients is in the range of 2-3 to prevent any subsequent cardiac event. These patients possess a challenge to the dentist in many ways, especially during oral surgical procedures, and these challenges include risk of sudden death, control of post-operative bleeding and pain.This article presents the dental management of a 60 year-old person with an ICD and concomitant anticoagulant therapy. The patient was on multiple medications and was treated for a grossly neglected mouth with multiple carious root stumps. This case report outlines the important issues in managing patients fitted with an ICD device and at a risk of sudden cardiac death. Keywords: Cardioverter Defibrillator, Arrhythmia, Warfarin, Dental extraction, INR